Social inequality in tooth loss: separate and joint effects of household income and dental visits. Issue 4 (2021) - Hach, Maria; Diderichsen, Finn; Christensen, Lisa B.; Lange, Theis; Hvidtfeldt, Ulla A.
No abstract available